2008
DOI: 10.1016/j.jprot.2008.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high-throughput IMS–IMS–MS approach for analyzing mixtures of biomolecules

Abstract: A high-throughput approach for biomolecule analysis is demonstrated for a mixture of peptides from tryptic digest of four proteins as well as a tryptic digests of human plasma. In this method a chipbased electrospray autosampler coupled to a hybrid ion mobility (IMS) mass spectrometer (MS) is utilized to achieve rapid sample analysis. This high-throughput measurement is realized by exploiting the direct infusion capability of the chip based electrospray with its rapid sample manipulating capability as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 51 publications
0
40
0
1
Order By: Relevance
“…Early studies by Jarrold and Clemmer studied proteins such as ubiquitin [12] (∼8.5 kDa) and cytochrome c [13] (∼12.4 kDa) to characterise collision cross-sections under a variety of physical conditions such as temperature, pH and solvent conditions. More recent efforts have achieved greater sample throughput of biomolecule mixtures [14], resolving power [15] or sensitivity [16], allowing lower abundance species to be investigated. Instrument development has been integral to these achievements.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies by Jarrold and Clemmer studied proteins such as ubiquitin [12] (∼8.5 kDa) and cytochrome c [13] (∼12.4 kDa) to characterise collision cross-sections under a variety of physical conditions such as temperature, pH and solvent conditions. More recent efforts have achieved greater sample throughput of biomolecule mixtures [14], resolving power [15] or sensitivity [16], allowing lower abundance species to be investigated. Instrument development has been integral to these achievements.…”
Section: Introductionmentioning
confidence: 99%
“…18,62 The specific conditions used in these studies are similar to those reported in our recent study of glycans. 30 General descriptions of theory and experiment that are valuable for understanding the concepts in this paper can be found elsewehere.…”
Section: Experimental Ims-ms Analysis Of Glycansmentioning
confidence: 58%
“…The instrument used in this study is a modified version of existing IMS-MS instruments described previously [21, 43, 44]. The electrospray ionization (ESI) source and all the components that come after the OMS regions are unchanged.…”
Section: Methodsmentioning
confidence: 99%